Gold(III) catalyzed stereoselective synthesis of dialkyl dihydrofuran acetates. (27th August 2021) - Behera, Sagarika; Bera, Nabakumar; Sarkar, Debayan
Abstract: A gold (III) catalyzed stereoselective cycloisomerization of 5-disubstituted-5-hydroxypent-2-yn alkanoate is described. The mild and efficient reaction condition delivers a series of di, tri- substituted dihydrofuran derivatives with high yields along with an impressive diastereoselectivity. The reaction proceeds via a double [3, 3] sigmatropic rearrangement with a concomitant 5- endo - dig cyclization encompassing an allenyl intermediate. Graphical abstract: Image 1